Development of the predator Podisus nigrispinus fed on Spodoptera frugiperda and Tenebrio molitor - Oliveira, Harley Nonato de; Pratissoli, Dirceu; Pedruzzi, Eder Pin; Espindula, Marcelo Curitiba (Pesquisa Agropecuaria Brasileira, 2004)
Nymphys of Podisus nigrispinus (Heteroptera: Pentatomidae) have been reared on Tenebrio molitor L. (Coleoptera: Tenebrionidae), in laboratory conditions. However, there are no reports on P. nigrispinus predation, in field or laboratory, on Spodoptera frugiperda (Lepidoptera: Noctuidae), one of the most damaging pests in crops in Brazil. This research had the objective to evaluate nymphal development and reproductive characteristics of the predator P. nigrispinus when reared on caterpillars of S. frugiperda and on larvae of T. molitor, in laboratory conditions. S. frugiperda provided a smaller longevity, higher egg production and viability to predator than T. molitor. The nutricional quality of this caterpillar improves the reproductive characteristics of the predator, so that its utilization as factitious host can increase mass production of this natural enemy.